PERAN PROGRAM BANYUWANGI MENGAJAR DALAM MENGURANGI KETIMPANGAN AKSES PENDIDIKAN DAN DAMPAKNYA TERHADAP PEMBANGUNAN EKONOMI DAERAH - Wahyudiono, Andhika (JURNAL KATARSIS, 2024)
The problem of inequality in access and quality of education in Banyuwangi is caused by the unequal distribution of resources, which affects the quality of human resources (HR) and the economy. The purpose of this study is to analyse inequality in access to education in remote areas and the role of education administration in addressing it. role of education administration in overcoming it. This research methodology uses a qualitative, literature-based approach to analyse qualitative, literature-based approach to analyse inequality in access to education and the impact of education administration on the regional economy. The results The results of this study show that collaboration between the government, the community and the private sector in the Banyuwangi Mengajar programme is crucial to private sector in the Banyuwangi Teaching Programme is essential to addressing education inequality in remote areas. The programme successfully programme has succeeded in improving the capacity of the teaching staff and ensuring equitable distribution of education resources. The research conclusions emphasise that this collaboration plays a crucial in improving access and quality of education in remote areas. The programme Banyuwangi Mengajar programme can strengthen synergies between parties, ensure equitable distribution of education resources and sustainably reduce education inequality, and sustainably reduce educational inequality. This research highlights the importance of an inclusive approach in education to build a better foundation for economic and social development in the area. a better foundation for economic and social development in underdeveloped areas. underdeveloped areas.